-100k+-30=-75-50k

Simple and best practice solution for -100k+-30=-75-50k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -100k+-30=-75-50k equation:


Simplifying
-100k + -30 = -75 + -50k

Reorder the terms:
-30 + -100k = -75 + -50k

Solving
-30 + -100k = -75 + -50k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '50k' to each side of the equation.
-30 + -100k + 50k = -75 + -50k + 50k

Combine like terms: -100k + 50k = -50k
-30 + -50k = -75 + -50k + 50k

Combine like terms: -50k + 50k = 0
-30 + -50k = -75 + 0
-30 + -50k = -75

Add '30' to each side of the equation.
-30 + 30 + -50k = -75 + 30

Combine like terms: -30 + 30 = 0
0 + -50k = -75 + 30
-50k = -75 + 30

Combine like terms: -75 + 30 = -45
-50k = -45

Divide each side by '-50'.
k = 0.9

Simplifying
k = 0.9

See similar equations:

| 6x+6x^2=12 | | (-7x^4y)(5x^2+9x^6y^3-3y^3)= | | -6=-7-n | | 33-y=20 | | 40+3x=(5x-10) | | .50x+.25(70)=37.5 | | x-(21)=9 | | -9k=126 | | 22+y=25 | | -7x^4y(5x^2+9x^6y^3-3y^3)= | | cos(2x)*cos(4x)= | | -9=126 | | 1.2-n+3.4=10 | | 2x-53=17 | | 2=t(28-4.9t) | | 0.25x+.05(6-x)=.10(-29) | | 3n-10=56 | | 3x^2+3y^2+18x-42y+162=0 | | 42=4x+6y | | (2x^3)+16=0 | | 4y-4+y+28=5+5y+25-3y | | 5(n-18)=10 | | p=10-4y+y^2 | | x^2-72x+100=0 | | 36x^3-15x^2+84x-35=0 | | 9x+12=5x+8 | | 2=t(20-4.9t) | | 6x+7=7x+6 | | 8x-52=2x+14 | | x^2-72x+256=0 | | 180=108(x+18) | | (12+8x)=1 |

Equations solver categories